Radiotherapy as a metastasis directed therapy for liver oligometastases - comparative analysis between CT-guided interstitial HDR brachytherapy and two SBRT modalities performed on double-layer and single layer LINACs - Bilski, Mateusz; Peszyńska-Piorun, Magdalena; Konat-Bąska, Katarzyna; Brzozowska, Agnieszka; Korab, Katarzyna; Wojtyna, Ewa; Janiak, Przemysław; Ponikowska, Julia; Sroka, Sylwia; Cisek, Paweł; Fijuth, Jacek; Kuncman, Łukasz (Frontiers in Oncology, 2024)
IntroductionSurgical resection is gold standard for treatment of liver metastasis, locally ablative techniques including computer tomography (CT)-guided interstitial high-dose-rate (HDR) brachytherapy (CT-BRT) and stereotactic body radiotherapy (SBRT) have gained prominence as alternatives, offering comparable outcomes in selected patients. We aim to compare CT-BRT and SBRT - based on dosimetric analysis.Material and methodsPatients who underwent CT-BRT for oligometastatic, ≤4cm liver metastases between 2018 and 2024 were eligible. SBRT plans for Halcyon (SBRTh) and TrueBeam (SBRTtb) were prepared virtually. In the CT-BRT group CTV was equal to PTV, for SBRTh and SBRTtb planning, a 5 mm margin was applied to CTV to create PTV. Dose calculation was carried out with the TG-43 algorithm for CT-BRT and Anisotropic Analytical Algorithm for SBRTh and SBRTtb group. Descriptive statistics were used to compare the data. The Wilcoxon pairwise order test was utilized to compare dependent groups.ResultsCT-BRT resulted in a more favorable dose distribution within PTVs for Dmean, D50, and D90, while SBRT showed better results for D98 and V27.5Gy. No significant differences were observed for V25Gy between CT-BRT and SBRTtb, but SBRTh favored over CT-BRT. For OARs, CT-BRT plans showed better values for V5, V10, and V11.6Gy in the uninvolved liver volume. There were no significant differences in dose distribution for the duodenum, bowel, and heart. SBRT modalities performed better in the kidney. CT-BRT had improved dose distribution in the esophagus, great vessels, ribs, skin, spinal cord, and stomach compared to SBRT.ConclusionsCT-BRT could be a viable alternative to SBRT for certain patients with liver malignancies.